Sodium Humate Alleviates Enterotoxigenic Escherichia coli-Induced Intestinal Dysfunction via Alteration of Intestinal Microbiota and Metabolites in Mice - Wang, Dong; He, Yanjun; Liu, Kexin; Deng, Shouxiang; Fan, Yuying; Liu, Yun (Frontiers in Microbiology, 2022)
Enterotoxigenic Escherichia coli (ETEC) can damage intestinal epithelial barrier function and lead to serious intestinal diarrhea in newborns and young animals. Sodium humate (HNa) is natural organic bioactive compound possessing antibacterial, anti-inflammatory, and anti-diarrheal properties. This study investigated the alleviative potential of HNa on the impaired intestinal barrier and intestinal inflammation, and regulatory effects on gut microbiota and metabolites in ETEC K88 infected mice. A total of 30 female mice were randomly assigned into three groups. The mice in the control and ETEC groups were gavaged with 0.2 mL of sterile saline, while the mice in the ETEC + HNa group were gavaged with 0.2 mL of 5% HNa, daily. On day 8, the mice in ETEC and ETEC + HNa group were challenged with ETEC K88. The trial lasted for 12 days. HNa administration elevated ETEC K88-induced body weight loss and ameliorated jejunum and colon pathological injury. HNa also reduced the levels of pro-inflammatory cytokines in the serum, jejunum, and colon. Additionally, HNa reduced intestinal barrier damage by up-regulating the expression of tight junction proteins (TJPs) and mucosal repair factors. 16s rDNA gene sequencing results showed that HNa increased the abundance of beneficial bacteria Lactobacillus, Prevotella_9, and Odoribacter but decreased the abundance of pathogenic bacteria Escherichia and Gastranaerophilales in the feces of mice. Moreover, metabolomic analysis revealed that the concentrations of 15 metabolites, the pathways of protein digestion and absorption, and propanoic acid metabolism were changed by HNa administration. In conclusion, HNa could alleviate ETEC K88-induced intestinal dysfunction through restoring intestinal barrier integrity, modulating gut microbiota and metabolites.